Gamma-Tocotrienol Protects the Intestine from Radiation Potentially by Accelerating Mesenchymal Immune Cell Recovery - Sarita Garg; Ratan Sadhukhan; Sudip Banerjee; Alena V. Savenka; Alexei G. Basnakian; Victoria McHargue; Junru Wang; Snehalata A. Pawar; Sanchita P. Ghosh; Jerry Ware; Martin Hauer-Jensen; Rupak Pathak (MDPI AG, 2019)
Natural antioxidant gamma-tocotrienol (GT3), a vitamin E family member, provides intestinal radiation protection. We seek to understand whether this protection is mediated via mucosal epithelial stem cells or sub-mucosal mesenchymal immune cells. Vehicle- or GT3-treated male CD2F1 mice were exposed to total body irradiation (TBI). Cell death was determined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Villus height and crypt depth were measured with computer-assisted software in tissue sections. Functional activity was determined with an intestinal permeability assay. Immune cell recovery was measured with immunohistochemistry and Western blot, and the regeneration of intestinal crypts was assessed with ex vivo organoid culture. A single dose of GT3 (200 mg/kg body weight (bwt)) administered 24 h before TBI suppressed cell death, prevented a decrease in villus height, increased crypt depth, attenuated intestinal permeability, and upregulated occludin level in the intestine compared to the vehicle treated group. GT3 accelerated mesenchymal immune cell recovery after irradiation, but it did not promote ex vivo organoid formation and failed to enhance the expression of stem cell markers. Finally, GT3 significantly upregulated protein kinase B or AKT phosphorylation after TBI. Pretreatment with GT3 attenuates TBI-induced structural and functional damage to the intestine, potentially by facilitating intestinal immune cell recovery. Thus, GT3 could be used as an intestinal radioprotector.